Magnetic properties of monoclinic lanthanide metaborates, Ln(BO2)3, Ln = Pr, Nd, Gd, Tb. (1st September 2017) - Mukherjee, P; Suard, E; Dutton, S E
Abstract: The bulk magnetic properties of the lanthanide metaborates, Ln (BO2 )3, Ln   =  Pr, Nd, Gd, Tb are studied using magnetic susceptibility, heat capacity and isothermal magnetisation measurements. They are found to crystallise in a monoclinic structure containing chains of magnetic Ln 3+ and could therefore exhibit features of low-dimensional magnetism and frustration. Pr(BO2 )3 is found to have a non-magnetic singlet ground state. No magnetic ordering is observed down to 0.4 K for Nd(BO2 )3 . Gd(BO2 )3 exhibits a sharp magnetic transition at 1.1 K, corresponding to 3D magnetic ordering. Tb(BO2 )3 shows two magnetic ordering features at 1.05 K and 1.95 K. A magnetisation plateau at a third of the saturation magnetisation is seen at 2 K for both Nd(BO2 )3 and Tb(BO2 )3, which persists in an applied field of 14 T. This is proposed to be a signature of quasi 1D behaviour in Nd(BO2 )3 and Tb(BO2 )3 .